Comparative evolution of the phenomenon of geography of sports on national and global levels - Marin CHIRAZI (Editura Universităţii din Oradea, 2019)
This study is a research of national and global evolution of literature on sports and geography with a view to emphasize emergence of a new category of study, least dealt with, whose impact on environment and society is tremendous. Sport is an inseparable component of society due to both its salubrious role through its effects and its necessary equipment and infrastructure. Sport activities are extremely diverse and most of the time they require special material conditions to practice it. This determines, while practice it, a relation of dependence to other fields as well: industrial, demographic, social, cultural, and political with local, national and global influences. Having in view optimisation of sport activities, from the perspective of inter-disciplinarity, a neighbouring field has been configured and developed and it has been called "geography of sports". Analysis of the specialised literature of the two fields (geography and sports) has led us to the conclusion that "geography of sports" has approached two main directions: geography of sports categories (it studies preference given to some sports in different areas), geography of sport infrastructure (it locates sport clubs, stadiums, sport facilities etc.) and geography of sport events (venues for organisation of sport events and their requirements). Also it has emphasised a series of studies on the influence of different geographic zones (mountains, seas, fields) on motor skills of the population, both from the point of view of preparation (athletic training) and from salubrious perspective.